Ninja turtles and Generation Y at work - Buik, Ann (Training and Development in Australia, 2008)
Retention and engagement issues are not of course exclusive to Generation Y - all employees will benefit from the emergence of a Generation Y "mindset", resulting in new leadership styles and more flexible work arrangements. However, the difference is that Generation Y employees will not wait around for what they want and will simply leave if they don't get it. Managers who understand the needs and motivators of Generation Y and use coaching and mentoring to develop and empower these future leaders will reap dividends in increased retention rates and high performance while they remain with the business. The results of workplace surveys consistently indicate that one of the main reasons Generation Y employees leave employers is that they didn't like or respect either their manager or the organisation. Generation Y don't want an old-style "command and control" manager who tells them what to do and expects them to do it without question. On the contrary, having grown up with Teenage Mutant Ninja Turtles, Power Rangers and Pokémon, whose central characters offered or relied heavily on the influence of a coach/mentor, Generation Y responds much better to coaching and mentoring in the workplace. Our future leaders will be drawn from Generation Y. The characteristics of leadership include courage, openness to change, adaptability, flexibility and the ability to collaborate and partner - the stereotypical attributes of Generation Y. Generation Y want role models of great leadership and look to their managers not only to "walk the talk" but to help them to develop their own leadership potential. Coaching provides a huge opportunity for managers to model effective leadership in the workplace and at the same time help Generation Yers to identify and develop their desired leadership skills and attributes. Generation Y represents a huge pool of talented, creative, innovative and optimistic talent in the workforce. Leaders of the future will be drawn from this pool of talent. Managers and leaders who coach Generation Y in a collaborative, equal coaching relationship will not only help these employees to maximise their potential and exceed their expectations of themselves, but in doing so will develop their own leadership skills and performance. When a company creates a coaching culture throughout the entire organisation and is seen as an "employer of choice", talented, highperforming Generation Y employees are more likely to stay longer or even return as leaders of the future.